2022
DOI: 10.3349/ymj.2022.63.8.717
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective National Study on Colonization Rate and Antimicrobial Susceptibility of Streptococcus agalactiae in Pregnant Korean Women, 2018–2020

Abstract: Purpose The prevalence of Group B Streptococcus (GBS) colonization in pregnant Korean women is increasing; however, nationwide studies are lacking. Therefore, we aimed to analyze regional colonization rates and antimicrobial susceptibility for GBS in pregnant Korean women through a nationwide survey. Materials and Methods From January 2018 to December 2020, data from the Seoul Clinical Laboratories on vaginal swab cultures were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Worldwide, macrolide resistant rates are also high in S. agalactiae. As occurred with other streptococci, Asian countries have the highest resistance prevalence, up to 70% in China in 2015 and 36% in Korea between 2018 and 2021 [86,87]. Nevertheless, high resistance rates were reported in the USA (55% of MR in the last decade) and some European countries with rates ranging from 17.5% in Denmark (2018) to 20-35% in Spain, Portugal, France and Belgium in 2019, and up to 48% in Italy in 2019 (Table 1) [88][89][90][91][92][93][94][95].…”
Section: Macrolide Resistance In β-Haemolitic Streptococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, macrolide resistant rates are also high in S. agalactiae. As occurred with other streptococci, Asian countries have the highest resistance prevalence, up to 70% in China in 2015 and 36% in Korea between 2018 and 2021 [86,87]. Nevertheless, high resistance rates were reported in the USA (55% of MR in the last decade) and some European countries with rates ranging from 17.5% in Denmark (2018) to 20-35% in Spain, Portugal, France and Belgium in 2019, and up to 48% in Italy in 2019 (Table 1) [88][89][90][91][92][93][94][95].…”
Section: Macrolide Resistance In β-Haemolitic Streptococcusmentioning
confidence: 99%
“…Nevertheless, high resistance rates were reported in the USA (55% of MR in the last decade) and some European countries with rates ranging from 17.5% in Denmark (2018) to 20-35% in Spain, Portugal, France and Belgium in 2019, and up to 48% in Italy in 2019 (Table 1) [88][89][90][91][92][93][94][95]. These MR rates are associated with a dominance of the MLS B phenotype related to both erm(B) and erm(TR) and associated with serotypes III, V, Ib and Ia (Table 2) [86][87][88][89][92][93][94][95][96][97]. Recently, an increase of macrolide resistance has been described in Portugal with rates of up to 35% [94] linked with the spread of a recombinant lineage of clonal complex (CC) 1 expressing type Ib serotype.…”
Section: Macrolide Resistance In β-Haemolitic Streptococcusmentioning
confidence: 99%
“…Du et al (Du et al, 2021) found that in Vietnamese pregnant women, the multidrug-resistance rate was 59.19%, with 8.46% of isolates resistant to six to seven antibiotics. Similarly, Bae et al (Bae et al, 2022) reported a nationwide GBS colonization rate of 10.6% in pregnant Korean women. Furthermore, Du et al (Van Du et al, 2021) highlighted the importance of considering the high rates of erythromycin, clindamycin, and multidrug resistance in GBS as a risk factor for neonates.…”
Section: Resistance To Erythromycin and Clindamycin In Gbs And Its Un...mentioning
confidence: 87%
“…However, this approach has been unsuccessful owing to a decrease in investment in the development of new antibiotics and the depletion of novel antibiotic candidates ( 3 ). Furthermore, antibiotic resistance rates among bacteria are increasing annually ( 4 6 ). The World Health Organization (WHO) declared that we are entering a post-antibiotic era where no antibiotics can treat MDR bacterial infections ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%